Manajemen Fisioterapi pada Post-Operative Ligamen Anterior Cruciatum - Irianto Irianto; Bustaman Wahab; Nur Ainun; Anastasya Fanny Sirenden; Gita Safirah Nuskin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Stabilization of the tibia when moving forward and rotational movements of the knee joint will be assisted by one of the ligaments in the knee joint, namely the Anterior Cruciate Ligament (ACL). This study aims to present physiotherapy management strategies to help reduce pain, prevent stiffness, increase muscle strength, decrease muscle spasms, increase the joint scope of motion, and overcome edema. The method used in this study is a case report. Primary data are obtained through auto anamnesis and physical examination. Holistic diagnosis assessment is carried out quantitatively from the study's beginning, process, and end. The result is that a 33-year-old male patient with a postoperative diagnosis of ACL underwent surgery on November 14, 2022, and has done therapy 7 times; the patient has experienced significant changes. It can be concluded that postoperative ACL rehabilitation can reduce edema and pain, increase muscle strength, and increase ROM. Finding interventions that can be applied to learning and modification of interventions is also recommended to assist in post-ACL reconstruction recovery to return to daily activities. The diagnosis and treatment of physiotherapy in patients are by the latest theories and research. In the evaluation, clinical improvement of patients and increased knowledge were obtained